Patient–physician communication about early stage prostate cancer: analysis of overall visit structure. (22nd December 2013) - Henry, Stephen G.; Czarnecki, Danielle; Kahn, Valerie C.; Chou, Wen‐Ying Sylvia; Fagerlin, Angela; Ubel, Peter A.; Rovner, David R.; Alexander, Stewart C.; Knight, Sara J.; Holmes‐Rovner, Margaret
Abstract: Background: We know little about patient–physician communication during visits to discuss diagnosis and treatment of prostate cancer. Objective: To examine the overall visit structure and how patients and physicians transition between communication activities during visits in which patients received new prostate cancer diagnoses. Participants: Forty veterans and 18 urologists at one VA medical centre. Methods: We coded 40 transcripts to identify major communication activities during visits and used empiric discourse analysis to analyse transitions between activities. Results: We identified five communication activities that occurred in the following typical sequence: 'diagnosis delivery', 'risk classification', 'options talk', 'decision talk' and 'next steps'. The first two activities were typically brief and involved minimal patient participation. Options talk was typically the longest activity; physicians explicitly announced the beginning of options talk and framed it as their professional responsibility. Some patients were unsure of the purpose of visit and/or who should make treatment decisions. Conclusion: Visits to deliver the diagnosis of early stage prostate cancer follow a regular sequence of communication activities. Physicians focus on discussing treatment options and devote comparatively little time and attention to discussing the new cancer diagnosis. Towards the goal of promoting patient‐centred communication, physicians should consider eliciting patient reactions after diagnosis delivery and explaining the decision‐making process before describing treatment options.